Light-patterning of synthetic tissues with single droplet resolution. - Booth, M; Restrepo Schild, V; Box, S; Bayley, J (Nature Publishing Group, 2017)
Synthetic tissues can be generated by forming networks of aqueous droplets in lipid-containing oil. Each droplet contains a cell-free expression system and is connected to its neighbor through a lipid bilayer. In the present work, we have demonstrated precise external control of such networks by activating protein expression within single droplets, by using light-activated DNA to encode either a fluorescent or a pore-forming protein. By controlling the extent of activation, synthetic tissues were generated with graded levels of protein expression in patterns of single droplets. Further, we have demonstrated reversible activation within individual compartments in synthetic tissues by turning a fluorescent protein on-and-off. This is the first example of the high-resolution patterning of droplet networks, following their formation. Single-droplet control will be essential to power subsets of compartments within synthetic tissues or to stimulate subsets of cells when synthetic tissues are interfaced with living tissues.